The Effectiveness of Process Approach Toward Students’ Writing Ability in Argumentative Text at MAS AL Barokah - Rahayu Aningsih; Rauldatul Husni; Riyadi Saputra (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2022)
The purpose of this study was to obtain empirical evidence about the effectiveness of the use of the Process Approach on the ability to write argumentative texts of students in the eleventh grade of MAS Al Barokah. The population of this study was the eleventh grade students of MAS Al Barokah with a total sample of 25 students. The method used in this study is a quantitative method using a pre-experimental design, one grub pretest-posttest. The research instrument used in this research is a set of written tests which are given at the beginning of the meeting and at the end of the meeting after the Process Approach is applied. The data from this study were analyzed using t-test. The results obtained from the research show that there are differences in student scores in writing argumentative texts using the Process Approach before and after being given treatment. The results shown from the post-test p-value is 0.000 with a significance level of 5% (0.05). In other words, it can be concluded if the p-value (0.000) < sig a=0.05 (5%). This proves that using the Process Approach is quite effective on the ability to write argumentative texts for eleventh graders at MAS Al Barokah for the 2021/2022 academic year